2021
DOI: 10.3389/fneur.2021.789254
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Diffusion Kurtosis Imaging in Detecting Delayed Brain Development of Premature Infants

Abstract: Objective: Preterm infants are at high risk of the adverse neurodevelopmental outcomes. Our aim is to explore the value of diffusion kurtosis imaging (DKI) in diagnosing brain developmental disorders in premature infants.Materials and Methods: A total of 52 subjects were included in this study, including 26 premature infants as the preterm group, and 26 full-term infants as the control group. Routine MRI and DKI examinations were performed. Mean kurtosis (MK), radial kurtosis (RK), fractional anisotropy (FA), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In (Zhao et al, 2021), kurtosis-related parameters, especially MK, showed to sensitively reflect the brain maturity of premature infants. Decreased MK values were registered in the preterm cohort due to the decreased density of cells and axon membranes associated with impaired brain development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In (Zhao et al, 2021), kurtosis-related parameters, especially MK, showed to sensitively reflect the brain maturity of premature infants. Decreased MK values were registered in the preterm cohort due to the decreased density of cells and axon membranes associated with impaired brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies show how higher-order diffusion models (e.g., Diffusion Kurtosis Imaging (DKI) (Zhao et al, 2021;Ouyang et al, 2019b;Shi et al, 2016), Neurite Orientation Dispersion and Density Imaging (NODDI) (Kelly et al, 2016) or Constrained Spherical Deconvolution (CSD) (Pannek et al, 2018)) may offer unique insight into the postnatal neurological development associated with differential degrees of preterm birth, thanks to their improved sensitivity to microstructural changes. Indeed, by relating the diffusion signal more directly and specifically to underlying cellular microstructural properties, these HARDI methods allow to investigate WM microstructure with higher levels of detail and to potentially give access to richer microstructural properties, thus increasing the diagnostic values of their derived measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on the assumption that water molecules diffuse freely and that diffusion only reflects the Gaussian distribution. It is unable to completely characterize tissue microstructure ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a novel diffusion-weighted technique of MRI, DKI may provide sensitive and comprehensive measures for the quantitative evaluation of microstructural changes of brain white matter ( 10 12 ). DKI exhibited improved specificity in detecting pathological changes in the developing brain ( 10 , 11 ). DKI may provide both diffusion metrics, such as fractional anisotropy (FA), as well as kurtosis parameters, including mean kurtosis (MK), which is specific parameter that cannot be expressed by DTI.…”
Section: Introductionmentioning
confidence: 99%